2018
DOI: 10.1002/anie.201807490
|View full text |Cite
|
Sign up to set email alerts
|

Auto‐regulated Protein Assembly on a Supramolecular Scaffold

Abstract: Controlled protein assembly provides a means to regulate function. Supramolecular building blocks, including rigid macrocycles, are versatile triggers of protein assembly. Now it is shown that sulfonato-calix[8]arene (sclx ) mediates the formation of cytochrome c tetramers in solution. This tetramer spontaneously disassembles at ≥2 equivalents of sclx , providing a remarkable example of auto-regulation. Using X-ray crystallography the sclx binding sites on cytochrome c were characterized. Crystal structures at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
174
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 65 publications
(181 citation statements)
references
References 53 publications
7
174
0
Order By: Relevance
“…These systems are characterized by bell‐shaped dose‐response curves, where there is a maximum concentration of ligand required to achieve peak response, above which the response is reduced . This effect was reported more than a century ago for antibodies (“prozone effect” or “hook effect”), and has since been observed in DNA transcription (“auto‐regulation”), heparin‐regulated enzyme activity (“template mechanism”),, scaffold proteins (“combinatorial inhibition”), phytate‐mediated protein precipitation,, and supramolecular control of protein assembly ,. Here, we refer to this property as auto‐regulated assembly.…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…These systems are characterized by bell‐shaped dose‐response curves, where there is a maximum concentration of ligand required to achieve peak response, above which the response is reduced . This effect was reported more than a century ago for antibodies (“prozone effect” or “hook effect”), and has since been observed in DNA transcription (“auto‐regulation”), heparin‐regulated enzyme activity (“template mechanism”),, scaffold proteins (“combinatorial inhibition”), phytate‐mediated protein precipitation,, and supramolecular control of protein assembly ,. Here, we refer to this property as auto‐regulated assembly.…”
Section: Introductionmentioning
confidence: 84%
“…This mechanism has been referred to as polysteric linkage,, contrasting with allosteric linkage in which protein conformation and dynamics are regulated by ligands. Recently, protein dimerization and higher order assembly has been engineered via synthetic molecules, including bivalent ligands and supramolecular scaffolds . Competitive inhibitors of these molecules can be used to control disassembly ,…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we have shown that calix[6]arene binding, in combination with imidazole coordination, results in significant structural rearrangement of cyt c . In the cyt c – sclx 6 crystal, the calixarene provides a scaffold that stabilizes the restructured Ω‐loop D mainly through complexation of Lys73 and Lys79. The loss of packing interactions has knock‐on effects for Ω‐loop C, which is disordered.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, highly porous crystalline architectures have been obtained with cyt c and sclx 8 . In one case a protein‐calixarene framework (PDB http://www.rcsb.org/pdb/search/structidSearch.do?structureId=6gd9) is mediated exclusively by the calixarene .…”
mentioning
confidence: 99%